2015
DOI: 10.1002/asia.201500401
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Intentionally Introduced Defects on Electrode Materials for Alkali‐Ion Batteries

Abstract: Simple defect modification is a powerful means to improve material intercalation capabilities. It has received considerable interest lately as it can directly alter both the chemical and structural characteristics; techniques of note include cationic disordering, amorphization, doping, partial cation reduction, and manipulation of intrinsic defects. Defects can reduce the stress and the electrostatic repulsion between adjacent oxygen layers, which can directly alter the migration energy and diffusion barriers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 84 publications
(189 reference statements)
0
41
0
Order By: Relevance
“…However, their synthesis can be time consuming, energy intensive, and costly. Besides, the storage capacity in crystalline materials is critically dependent on several factors including orientation of the crystallites, exposure of electrochemically active facets, phase transitions, and structural stability . Generally, the charge storage mechanism of these kinds of material is based on guest ion insertion/extraction during the charge/discharge process.…”
Section: Introductionmentioning
confidence: 99%
“…However, their synthesis can be time consuming, energy intensive, and costly. Besides, the storage capacity in crystalline materials is critically dependent on several factors including orientation of the crystallites, exposure of electrochemically active facets, phase transitions, and structural stability . Generally, the charge storage mechanism of these kinds of material is based on guest ion insertion/extraction during the charge/discharge process.…”
Section: Introductionmentioning
confidence: 99%
“…A general approach to enhance its surface electronic conductivity is to form composites with electronically conductive materials, although the synthesis is always complicated and the volume energy density may be reduced. Another strategy to tune the electrical conductivity and electrochemical reactions of LVO is by introducing ionic defects . Oxygen vacancies, for example, have been demonstrated to improve the specific capacity and rate performance of LVO …”
Section: Introductionmentioning
confidence: 99%
“…Another strategy to tune the electricalc onductivity and electrochemical reactions of LVOi s by introducing ionic defects. [24,25] Oxygen vacancies, for example, have been demonstrated to improvet he specific capacity and rate performance of LVO. [26][27][28] In this work, we introduced surface oxygen vacancies into LVOt hrough annealing in hydrogen and studied the impact on the lithium ion intercalation properties.…”
Section: Introductionmentioning
confidence: 99%
“…For close-packed metal oxide electrode system, electrodes with disordered cation or anion sites, accompanied accordingly with the changes of cation/anion vacancies and partial reduction of transition metal, have shown much enhanced storage capacity in Na 1.25+x V 3 O 8 , VFe 2 O x and LaMnO 3 electrode materials2021222324. Ceder's group reported that cation-disordered Li 1.2 Mo 0.47 Cr 0.3 O 2 compounds, in which Li, Mo and Cr are disordered within the transition metal layer while the lateral stacking is well maintained and oxygen stacking is also well maintained in ABCABCABC sequences, have shown a modified local environment for the transition metal ions, and therefore provided a lower percolation threshold of Li-ions transport so that Li-ion can diffuse easily without directly contacting the transition metal framework on the atomic scale22.…”
mentioning
confidence: 99%